Evaluation of the Proximity of Root Apices of Maxillary Posterior Teeth to the Maxillary Sinus Floor using CBCT among Different Age Groups: A Retrospective Study - Nadia Rasool; S. Vidhyadhara Shetty; Sajad A. Buch; Prathap MS Nair; S Kalaichelvan; Nishi Jayasheelan (Journal of Pharmacy and Bioallied Sciences)
Aim: The increased thickness of the Schneiderian membrane under pathological conditions may result in a thickness of up to 3 mm, thereby making it evident on the radiograph. Therefore, knowing that a thorough understanding of the anatomical correlation between maxillary sinus floor (MSF) and maxillary teeth is indispensable for the management of cases; this research was undertaken to evaluate the proximity of root apices of the maxillary posterior (RAMP) teeth to the MSF using cone-beam computed tomography (CBCT) among different age groups of the Indian population. Methods: CBCT scans of 150 patients were obtained from the institute’s database based on strict inclusion and exclusion criteria; such that an equal number of samples were obtained in the following three age groups: Group 1 – Young group (20–44 years), Group 2 – Middle age (45–59 years), Group 3 – Elderly (60–70 years). CBCT images were assessed in multiple cross-sections using Planmeca Romexis software to evaluate the vertical relationship between the RAMP teeth and the MSF. All values thus obtained were subjected to statistical analysis. Results: Of a total of 153 subjects included in our study, the number of males and females were 80 (52.3%) and 73 (47.7%), respectively, in the age group of 17–70 years where the mean age (and standard deviation) was 35.4 (12.4) years. The mesial, distal, and palatal root apices, respectively, of the maxillary second molar were closest to the MSF. Conclusion: Based on the observations, on comparing both sides, the difference noted in the roots of the maxillary first premolar – both buccal and palatal was statistically significant; but the influence of age and sex were found to be non-significant.